Enhancing School Administration in Rural South African Schools: Challenges and Opportunities-Using the Scooping Review Method - Ajani, Oluwatoyin A.; Dlomo, Sibongamandla (Research in Social Sciences and Technology, 2025)
This scoping review investigates the deployment and operational challenges of the South African School Administration and Management System (SA-SAMS) within rural secondary schools in the iLembe District. Aiming to understand the integration of Information and Communication Technology (ICT) in educational administration, this review analyses existing literature from 2008 to 2024 to map the effectiveness and obstacles encountered by SA-SAMS. Rural schools often need help adopting technological innovations due to inadequate ICT infrastructure, limited access to technology, and a deficit in training and support for educators and administrators. The review highlights that while SA-SAMS is designed to enhance administrative efficiency and improve data management, its implementation needs to be improved by these systemic issues, complicating its potential benefits. Furthermore, using the Technology Acceptance Model (TAM), the review identifies a need for targeted interventions, including enhanced training programmes, better ICT resource allocation, and infrastructure development. Overcoming these challenges could improve educational outcomes by enabling more efficient school management practices. This review contributes to the broader discourse on educational technology integration in rural settings, providing a foundation for policy recommendations and future research to optimise the use of SA-SAMS in improving school administration.